Chiral Phosphinoferrocenyl‐Calixarenes. Issue 20 (15th June 2016) - Karpus, Andrii; Yesypenko, Oleksandr; Boiko, Vyacheslav; Poli, Rinaldo; Daran, Jean‐Claude; Voitenko, Zoia; Kalchenko, Vitaly; Manoury, Eric
Abstract : The Mitsunobu alkylation of 4‐ tert ‐butylcalix[4]arene with ( S )‐(2‐diphenylthiophosphinoferrocenyl)methanol followed by desulfuration of the thiophosphine unit using tris(dimethylamino)phosphine afforded enantiomerically pure calixarene mono‐ and di(ferrocenylphosphine) ligands in high yields. The calixarene mono(ferrocenylphosphine) ligands exhibited good catalytic activity but low atropoenantioselectivity when used in the asymmetric Suzuki–Miyaura coupling reaction of 1‐naphthaleneboronic acid and 1‐bromo‐2‐methylnaphthalene. However, the di(ferrocenylphosphine) ligand displayed both good catalytic activity and enantioselectivity ( ee values up to 86 %) when employed in the asymmetric Tsuji–Trost allylic alkylation of 1, 3‐diphenylprop‐2‐enyl acetate with dimethyl malonate. Abstract : The Mitsunobu alkylation of 4‐ tert ‐butylcalix[4]arene and ( S )‐(2‐diphenylthiophosphinoferrocenyl)methanol followed by desulfuration gave enantiomerically pure calixarene mono‐ and di(ferrocenylphosphine) ligands. These ligands have good catalytic activity, but the di(ferrocenylphosphine) ligand also showed good enantioselectivity (up to 86 % ee ) in an asymmetric Tsuji–Trost allylic alkylation.